Britain, France and the financing of the First World War - Horn, Martin, 1959- 1959- (McGill-Queen's Univ. Press, 2002)
"Fighting the First World War consumed lives, material, and money. Millions died; more suffered. By war's end, the political map of Europe had been redrawn as empires disappeared and new states arose. Britain, France, and the Financing of the First World War traces the financial contours of the war, showing that victory flowed from the ability to arm and feed mass armies as well as the capacity to raise money. Britain financed the war not only to win but also to preserve its prewar financial dominance: France financed it to survive and to ensure that the stability of the Third Republic was not threatened."--BOOK JACKET.